2013
DOI: 10.1155/2013/104892
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Benefits of an Adherence Monitoring Program in the Management of Secondary Hyperparathyroidism with Cinacalcet: Results of a Prospective Randomized Controlled Study

Abstract: Background/Aims. One of the causes of uncontrolled secondary hyperparathyroidism (sHPT) is patient's poor drug adherence. We evaluated the clinical benefits of an integrated care approach on the control of sHPT by cinacalcet. Methods. Prospective, randomized, controlled, multicenter, open-label study. Fifty hemodialysis patients on a stable dose of cinacalcet were randomized to an integrated care approach (IC) or usual care approach (UC). In the IC group, cinacalcet adherence was monitored using an electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…Four studies [8, 11, 24, 51] indicated that they were partly or fully supported by pharmaceutical sponsors, whereas 20 studies were funded by public organisations, including universities. No information on funding source was provided in twelve studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies [8, 11, 24, 51] indicated that they were partly or fully supported by pharmaceutical sponsors, whereas 20 studies were funded by public organisations, including universities. No information on funding source was provided in twelve studies.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of standardized methods to measure adherence in these domains, contributes to the reported variations in the rate of non-adherence, and the difficulty of precisely estimating the effectiveness of interventions to improve adherence [3, 5]. Methods of measuring adherence vary across studies and include indirect measures, such as self-reported adherence [6, 7]; direct measures such as pill counts or electronic medication event monitoring system (MEMS) [8], and attendance in dialysis sessions [9]; as well as surrogate measures such as inter-dialytic weight gain [10, 11] or biochemical parameters, which include phosphate and potassium levels [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that, after six months of follow-up, 84% of the patients submitted to the IC group achieved satisfactory parathormone levels, compared to 55% of the patients in the habitual care group. (11) At a conservative treatment outpatient clinic in the city of Rio de Janeiro, the need was noticed to advance in the patient approach strategies to improve their treatment adherence. A collective strategy was adopted, which consisted of a waiting room debate mediated by health professionals; and an individual strategy consisting of a CKD monitoring card inspired by the child monitoring care, making it easier to visualize the progression of the disease, in addition to other aspects of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Cinacalcet is also a substrate and inhibitor of cytochrome P450 (CYP) isoenzymes and requires careful management of concomitant medications to avoid drug–drug interactions . Furthermore, high pill burden in CKD dialysis can increase the challenges of compliance with self‐administered drugs . There is a need for a calcimimetic given by a more convenient route of administration for patient adherence, without drug–drug interaction potential, and one that can sustain PTH‐lowering effects to enable less frequent dosing.…”
mentioning
confidence: 99%